Thermal Stress Interacts With Surgeonfish Feces to Increase Coral Susceptibility to Dysbiosis and Reduce Tissue Regeneration - Ezzat, Leïla; Merolla, Sarah; Clements, Cody S.; Munsterman, Katrina S.; Landfield, Kaitlyn; Stensrud, Colton; Schmeltzer, Emily R.; Burkepile, Deron E.; Vega Thurber, Rebecca (Frontiers in Microbiology, 2021)
Dysbiosis of coral microbiomes results from various biotic and environmental stressors, including interactions with important reef fishes which may act as vectors of opportunistic microbes via deposition of fecal material. Additionally, elevated sea surface temperatures have direct effects on coral microbiomes by promoting growth and virulence of opportunists and putative pathogens, thereby altering host immunity and health. However, interactions between these biotic and abiotic factors has yet to be evaluated. Here, we used a factorial experiment to investigate the combined effects of fecal pellet deposition by the widely distributed surgeonfish Ctenochaetus striatus and elevated sea surface temperatures on microbiomes associated with the reef-building coral Porites lobata. Our results showed that regardless of temperature, exposure of P. lobata to C. striatus feces increased alpha diversity, dispersion, and lead to a shift in microbial community composition – all indicative of microbial dysbiosis. Although elevated temperature did not result in significant changes in alpha and beta diversity, we noted an increasing number of differentially abundant taxa in corals exposed to both feces and thermal stress within the first 48h of the experiment. These included opportunistic microbial lineages and taxa closely related to potential coral pathogens (i.e. Vibrio vulnificus, Photobacterium rosenbergii). Some of these taxa were absent in controls but present in surgeonfish feces under both temperature regimes, suggesting mechanisms of microbial transmission and/or enrichment from fish feces to corals. Importantly, the impact to coral microbiomes by fish feces under higher temperatures appeared to inhibit wound healing in corals, as percentages of tissue recovery at the site of feces deposition were lower at 30°C compared to 26°C. Lower percentages of tissue recovery were associated with greater relative abundance of several bacterial lineages, with some of them found in surgeonfish feces (i.e. Rhodobacteraceae, Bdellovibrionaceae, Crocinitomicaceae). Our findings suggest that fish feces interact with elevated sea surface temperatures to favor microbial opportunism and enhance dysbiosis susceptibility in P. lobata. As the frequency and duration of thermal stress related events increase, the ability of coral microbiomes to recover from biotic stressors such as deposition of fish feces may be greatly affected, ultimately compromising coral health and resilience.